1993
DOI: 10.1002/hep.1840180627
|View full text |Cite
|
Sign up to set email alerts
|

Increased benzodiazepine-like activity is neither necessary nor sufficient to explain acute hepatic encephalopathy in the thioacetamide-treated rat

Abstract: Increased levels of natural benzodiazepine receptor agonists, produced in the body (endogenous) or ingested with food (exogenous) have been proposed as one of the factors causing hepatic encephalopathy in both experimental animals and human subjects. However, the divergent response of hepatic encephalopathy to benzodiazepine antagonists sheds doubt on this attractive hypothesis. Acute liver failure was induced in male Sprague-Dawley rats (n = 17) with intraperitoneal thioacetamide (600 mg/kg/day for 3 days) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…Previous studies showed that low nanomolar concentrations of allopregnanolone or THDOC increase the binding of 3 H-muscimol to normal rat brain cortical membranes, enhance muscimol-stimulated 36 Cl ) uptake in rat cerebral cortical synaptosomes, and increase GABA-activated chloride conductance in cultured neurons. 35,36 There is an increasing body of evidence to suggest an involvement of neurosteroids in brain complications of liver diseases. Together, these findings demonstrate that brain accumulation of allopregnanolone and THDOC in PCA rats activates the GABA-A receptor complex, thus offering an explanation for the notion of Ôincreased GABAergic toneÕ in HE.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that low nanomolar concentrations of allopregnanolone or THDOC increase the binding of 3 H-muscimol to normal rat brain cortical membranes, enhance muscimol-stimulated 36 Cl ) uptake in rat cerebral cortical synaptosomes, and increase GABA-activated chloride conductance in cultured neurons. 35,36 There is an increasing body of evidence to suggest an involvement of neurosteroids in brain complications of liver diseases. Together, these findings demonstrate that brain accumulation of allopregnanolone and THDOC in PCA rats activates the GABA-A receptor complex, thus offering an explanation for the notion of Ôincreased GABAergic toneÕ in HE.…”
Section: Discussionmentioning
confidence: 99%
“…64 However, negative reports have subsequently appeared. 65,66 It has been suggested that the beneficial effects of flumazenil that appear to occur in a sub-group of patients may relate to allosteric effects on the neurosteroid modulatory site that is adjacent to the benzodiazepine site on the GABA-A receptor complex. 67 This hypothesis has not been tested in ALF.…”
Section: Other Neuropharmacological Approachesmentioning
confidence: 99%
“…However, two laboratories, one in Mon treal [27,28] and another in Switzerland, have had difficulty in detecting BZs [29], What must be understood is that these com pounds are lipophilic and protein bound. Thus, extraction procedures to process the original matrix (sample) have to be designed to take these properties into account.…”
Section: Bz Hypothesismentioning
confidence: 99%
“…Of course, increases of brain GABA in critical brain subregions could arise in the CNS rather than be transported in from the blood. We noted in some simple experiments a number of years ago that slight 2-to 3-fold increases in 24 Dig Dis 1996:14<suppl I ): [20][21][22][23][24][25][26][27][28][29] Mulien/Kaminsky-Russ brain GABA occurred after induction of se vere hyperammonemia by urease administra tion. However, this field of research has be come somewhat dormant in the last few years.…”
Section: Status and Future Of Existing Hypothesismentioning
confidence: 99%